Common Evil and Historical Reality. The Negativity of Today’s World from the Thought of Ignacio Ellacuría (Andamios, Revista de Investigación Social, 2024)
The concept of “common evil” is central to Ellacuría’s work, however, it has been one of the least studied. It is a concept that was developed in the maturity of his intellectual proposal, and that synthesizes and applies other dimensions of his thought that have been more studied. This text focuses on showing the relevance and validity of the “common evil” by relating the approach of the concept in its origins with some features of the historical configuration of the world today; that is, it aims to show the validity of Ellacurian thought to identify and continue thinking about the negativity of the current world to try to be up to the task of taking charge of reality.
Keywords: Ellacuría; common evil; historical reality; negativity; critical theory